(untitled) (American Journal of Islam and Society, 1991)
Abstract The influx of Muslim immigrants into America has become steady in the last decade, a development which raises the need for a theoretical outlook delineating a model of an Islamic-controlled process of assimilation. Using Gordon’s model of assimilation, the paper suggests an Islamic position regarding each of his seven types and stages of assimilation. In respect to cultural assimilation, the paper advocates an interactive process of assimilation on the level of extrinsic cultural traits. Such a process utilizes six filtration procedures regarding different kinds of American cultural artifacts. But on the level of intrinsic cultural traits, the paper suggests a counterassimilation position, and considers it a cornerstone in keeping the originality of Islam. As to identificational assimilation, the paper defines Islamic boundaries relevant to each of its three components: ethnic, national, and racial. The paper discusses behavior-receptional and attitude-receptional types of assimilation in light of patterns of behavior that affect such reciprocity. The paper argues that civic assimilation is a crucial area where much of the Muslim community’s efforts could be invested. Finally, the paper briefly discusses marital assimilation and structural assimilation. Introduction Assimilation is an important subject that deserves careful consideration from minorities, marginal groups, and immigrants. The position of a group on assimilation has far-reaching effects on its present and future, as well ...